2015
DOI: 10.1002/jso.23854
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection versus transarterial chemoembolization for BCLC stage C hepatocellular carcinoma

Abstract: SR provides significantly better long-term survival than TACE in patients with BCLC stage C HCC, and should be an integral part in the management of advanced HCC. Multidisciplinary approaches for these patients and further amendment to the BCLC classification scheme are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…Among the remaining 27 studies, eight studies were reported from three identical institutions and shared overlapping periods and populations. Therefore, we chose the more recent and comprehensive data sets . Additionally, four studies were excluded after quality assessment (modified MINORS score <12).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the remaining 27 studies, eight studies were reported from three identical institutions and shared overlapping periods and populations. Therefore, we chose the more recent and comprehensive data sets . Additionally, four studies were excluded after quality assessment (modified MINORS score <12).…”
Section: Resultsmentioning
confidence: 99%
“…The details and reasons for exclusion requiring consensus between the authors are described in http://onlinelibrary.wiley.com/doi/10.1002/hep.29883/suppinfo. Finally, 18 studies reporting PH versus TACE in BCLC stage B or stage C patients were included in the systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with A0 in stage C, defined as C1, are suggested to receive resection, leaving patients with moderate to severe cirrhosis. Liu et al study demonstrated a better overall survival of surgical resection than transarterial chemoembolization (TACE) in HCC patients with BCLC stage C [26]. LT is the optimal treatment even for small, otherwise resectable HCC.…”
Section: Discussionmentioning
confidence: 99%